Bullying Pada Remaja : Apa Sajakah Dampaknya Terhadap Psikologis dan Prestasi Akademik Korban? - Dewi, Putu ayu ratih kumala; Wilani, Ni Made Ari (Universitas Dhyana Pura, 2025)
Bullying is an action carried out by a group or a particular individual that aims to hurt or frighten others. This harassment or Bullying case still occurs today, one of them in Indonesia. Based on data from the Indonesian Child Protection Commission (KPAI), that from 2011 - 2018 showed an increase each year. During the 2016-2020 period the Indonesian Child Protection Commission (KPAI) had received complaints from 480 children who were victims of Bullying at their schools. Seeing this, the preparation of this literature aims to provide an understanding to the reader about the dangers or negative impacts of Bullying on victims. The results showed that the impact of Bullying on the psychological victims was a decrease in self -confidence, anxiety, not wanting to get along, not excited, sad, angry, hated himself even to the tendency of depression. While the impact on the victim's academic achievement is, a decrease in learning motivation.